Multiple myeloma following bone metastasis of renal cell carcinoma: a case report - Yu, Hong; Zhang, Shengnan; Feng, Xiaohui; Gao, Feng (Frontiers in Endocrinology, 2023)
Backgr ound: The clinical manifestations of multiple myeloma (MM) and bone metastatic tumor are both systemic bone pain, which is difficult to distinguish from imaging manifestations, leading to misdiagnosis and missed diagnosis.Case summar y: We reported a man with a unique case, whose tumors were MM with bone metastatic tumor of clear cell renal cell carcinoma (CCRCC). Computed tomography (CT) showed multifocal osteolytic bone destruction, while magnetic resonance imaging (MRI) showed multifocal bone marrow infiltration with soft tissue mass. Pathology and immunohistochemistry established the diagnosis in the coexistence of myeloma with bone metastatic tumor of CCRCC in spine.Immunotherapy and systemic chemotherapy were adopted in clinic, and vertebral decompression was performed after anemia was corrected. This case with MM and bone metastatic tumor of clear cell renal cell carcinoma (CCRCC) received the radiotherapy and immunotherapy, and acquired satisfying outcome after one year of follow-up.Conclusions: It is difficult to differentiate MM and bone metastatic tumor on imaging, especially when there are bone lesions at the same time, which is easy to miss diagnosis and needs to be comprehensively evaluated in combination with functional procedures, clinical laboratory tests and histopathology.